The Influence of Burnout, Workload and Work-Life Balance on Employee Performance - Setyanti, Sri Wahyu Lely Hana; Fagastia, Inas Rana; Sudarsih, Sudarsih (Budapest International Research and Critics University, 2022)
This study aims to determine and analyze the influence of burnout, workload, and work-life balance on the performance of employees at Bank Jatim Jember. The variables used in this study are burnout, workload, work-life balance, and performance. The population in this study is all employees who worked at Bank Jatim Jember 58 respondents. The sampling technique used is census sample technique because the population is less than 100 people, then all populations are used as samples, the sample is 58 respondents. The analytical tool used is multiple linear regression. The results showed that burnout and workload have a negative and significant influence on employee performance, while the work-life balance has a positive and significant effect on performance.